2009
DOI: 10.1264/jsme2.me08538
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene terephthalate) Polymer Surfaces as a Substrate for Bacterial Attachment and Biofilm Formation

Abstract: Plastic debris causes extensive damage to the marine environment, largely due to its ability to resist degradation. Attachment on plastic surfaces is a key initiation process for their degradation. The tendency of environmental marine bacteria to adhere to poly(ethylene terephthalate) (PET) plastic surfaces as a model material was investigated. It was found that the overall number of heterotrophic bacteria in a sample of sea water taken from St. Kilda Beach, Melbourne, Australia, was significantly reduced afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(64 citation statements)
references
References 20 publications
2
62
0
Order By: Relevance
“…Despite recognition of the role and importance of sediments as a sink for the accumulation of plastic debris [7,9,12,16,17], previous research into the interactions between marine microorganisms and plastic debris has focused on investigation of microbial interactions with polymers in the water column [14,21,22,24-28]. While a prior study has reported a significant increase in the number of polyethylene-associated bacteria following three weeks of exposure in seawater [25] and the abundance of rod-shaped (Bacillus) bacteria on plastic surfaces in the North Pacific Gyre has recently been determined [27], the Q-PCR data reported herein provide the first quantitative evaluation of the potential for bacterial attachment onto LDPE fragments within coastal marine sediments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recognition of the role and importance of sediments as a sink for the accumulation of plastic debris [7,9,12,16,17], previous research into the interactions between marine microorganisms and plastic debris has focused on investigation of microbial interactions with polymers in the water column [14,21,22,24-28]. While a prior study has reported a significant increase in the number of polyethylene-associated bacteria following three weeks of exposure in seawater [25] and the abundance of rod-shaped (Bacillus) bacteria on plastic surfaces in the North Pacific Gyre has recently been determined [27], the Q-PCR data reported herein provide the first quantitative evaluation of the potential for bacterial attachment onto LDPE fragments within coastal marine sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Early observations of the microbial colonization of microplastics in seawater reported the isolation of ‘rod shaped Gram-negative bacteria’ from ~0.5 mm polystyrene spherules [14] and the presence of diatoms on plastic fragments in the Sargasso Sea [1]. Culture-based seawater microcosm studies have also demonstrated microbial attachment to polyethylene terephthalate [24] and polyethylene plastic bags [25]. Moreover, experiments using molecular fingerprinting and 16S rRNA gene clone sequencing analyses have identified Roseobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…The surface topography of eroded PE is rough with pronounced cavities and appears substantially altered compared to virgin pellets. This uneven surface might explain the affinity of marine plastic particles for different microbes (Webb et al, 2009;Barnes, 2002) and their tendency for biofouling (Muthukumar et al, 2011;Artham et al, 2009;Sudhakar et al, 2007). The surface of beached PP pellets is not as rough as that of the beached PE pellets and looks more cracked than altered.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Currently, there are four Thalassospira strains reported to have their full genomes sequenced (814). Strain NP3b2 T was isolated from an enrichment experiment selecting for strains that degrade poly(ethylene terephthalate) (PET) from seawater collected from the first meter below the water’s surface at St. Kilda Beach, Port Phillip Bay, Tasman Sea, Victoria, Australia (15). The specific location of the studies (GPS coordinates) was 37°51′50″ S 144°58′55″ E. The analyses of the genome of this novel Thalassospira species will stimulate further research on the metabolite activity, organic pollutant degradation, physiological and ecological functions, and evolution of the bacteria of the genus Thalassospira .…”
Section: Genome Announcementmentioning
confidence: 99%